LAUNCHING PRODUK KERUPUK DAN SERTIFIKASI HALAL UPAYA MENINGKATKAN EKONOMI DAN UMKM DESA TLAGAH - Takwallo; Suratin Lukmana; Ulfatus Sholiha; Khofifah; Mawaddah; Ernawati; Sama’un; Mohammad Lutfianto (DEVELOPMENT: Journal of Community Engagement, 2026)
This community service program focused on developing community micro-enterprises through the launch of cracker products and assistance in the halal certification process. Implementation methods included initial observation, outreach, production assistance, packaging, marketing, and education on the importance of halal certification for business owners. The results showed that the cracker product launch increased the selling value and competitiveness of local products, while the halal certification assistance increased business owners' understanding of halal product standards and opened up broader marketing opportunities. This program had a positive impact on improving product quality and increasing awareness among UMKM  of the importance of legality and consumer trust. Therefore, this community service program is expected to encourage the sustainability of local cracker businesses and improve the welfare of the local community.